Battling hawkers’ and consumers’ resistance to change: The course of digitalisation never did run smooth (A) and (B) - LAU, Yi Meng (Institutional Knowledge at Singapore Management University, 2025)
Second-generation hawker Melvin Chew decided to set up the Hawkers United – Dabao 2020 Facebook group on April 7, 2020 after the Singapore government announced that given the worsening COVID-19 pandemic in Singapore, dining in at hawker centres, and all other food and beverage (F&B) establishments would be banned. The Facebook group would allow hawkers to post their offerings, promotions, and takeaway or delivery options. Customers could also join it to pre-order food from these hawkers. Chew decided to start this group to help his fellow hawkers, and provide an alternative to food delivery platforms that charged prohibitive commissions. However, there were several barriers preventing hawkers from going digital, such as practical difficulties encountered when adopting digital tools and the lack of digital and verbal literacy, particularly among some elderly hawkers. Despite the ongoing effort to encourage Singaporeans to go cashless, some hawkers and consumers were less tech-savvy, and therefore apprehensive about making or receiving digital payments. It did not help that there were frequent bank outages in Singapore in 2023 and 2024, and consumers who had become used to cashless payments were caught off-guard when cashless payments became unavailable. The lack of interoperability among the various digital payment systems in Singapore has highlighted the fragmented nature of the country’s payment ecosystem, causing greater inconvenience for consumers. This case is intended for use in a digital transformation course in an undergraduate information systems programme. Students should be able to achieve the following learning objectives: evaluate the extent of over-reliance on digital payments, propose how banks can enhance the resilience of their digital payment systems, pinpoint initiatives to facilitate seamless cashless payment services, and assess the importance of interoperability for the payment ecosystem.